Zhoushi Qi Ling decoction inhibits the progression of castration-resistant prostate cancer in vivo by regulating macrophage infiltration via IL6-STAT3 signaling - Hongwen Cao; Dan Wang; Renjie Gao; Lei Chen; Yigeng Feng; Peng Sun (Journal of Traditional and Complementary Medicine, 2024)
Background and aim: Prostate cancer is a leading malignant tumor in men, associated with a high rate of mortality. Androgen deprivation therapy is commonly used to treat prostate cancer, which contributes to the progression of castration-resistant prostate cancer (CRPC). The current therapy has a low survival rate in patients with CRPC. Our study aims to develop a novel effective approach for CRPC treatment and improve survival benefits. Experimental procedure: CRPC cell line PC-3-Luc expressing luciferase and the CRPC cell line PC-3-IL6-Luc stably overexpressing IL-6 were used to establish the xenograft tumor mouse model. The tumor was monitored weekly using Bioluminescence imaging. Infiltrated macrophages were quantified by fluorescence-activated cell sorting using flow cytometry. IL6 mRNA level was determined using quantitative real-time PCR. The protein levels of total STAT3 and phosphorylated STAT3 were determined using Western blot. Results and conclusion: Zhoushi Qi Ling decoction (ZQD) treatment significantly reduced PC3 the xenograft tumor progression and the number of infiltrated macrophages when compared with saline treatment. IL6 mRNA level was remarkedly suppressed by ZQD treatment. Notably, the protein level of phosphorylated STAT3 was significantly decreased in PC3 the xenograft tumor treated with ZQD compared to saline treatment. Our findings demonstrated that ZQD treatment significantly reduced the progression of prostate cancer, evidenced by the reduced population of infiltrated macrophages and the inhibition of the IL6/STAT3 pathway.